The novel HLA‐A*31:191 allele was identified in a Chinese platelet donor. (24th September 2021) - Yu, Qiyue; Song, Jing; Zhang, Yanke; Li, Haoru; Zhu, Faming
Abstract : HLA‐A*31:191 differs from HLA‐A*31:01:02:01 by one single nucleotide substitution at nucleotide 74.